2022
DOI: 10.1177/14644207221145463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acacia concinna and Vachellia nilotica seed nanopowder on the properties of short Turkish hemp–reinforced epoxy composites

Abstract: The study intends to examine the physical, mechanical, and moisture (water) absorption properties of Acacia concinna seed powder (ACSP) and Vachellia nilotica seed powder (VNSP) individually incorporated with short Turkish hemp (STH) natural fiber–reinforced composites (NFRCs) hybridized with epoxy matrix. ACSP and VNSP of size 30–40 nm were amalgamated with epoxy matrix in varying weight proportions (0, 2.5, 5, 7.5, and 10 wt%), and the composite laminates were stacked manually followed by hydraulic compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…During the fabrication process, LOCM was consistently added as a filler, with varying weight fractions ranging from 0% to 10%. According to the literature, 16,17 when seed powders exceed 10 wt%, they have a tendency to create voids in the material, resulting in increased brittleness. The weight fractions were incremented by 2.5%, as indicated in Table 1.…”
Section: Fabrication Of Flax/locm Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…During the fabrication process, LOCM was consistently added as a filler, with varying weight fractions ranging from 0% to 10%. According to the literature, 16,17 when seed powders exceed 10 wt%, they have a tendency to create voids in the material, resulting in increased brittleness. The weight fractions were incremented by 2.5%, as indicated in Table 1.…”
Section: Fabrication Of Flax/locm Compositesmentioning
confidence: 99%
“…However, surpassing these microcellulose fillers content threshold (7.5 wt% LOCM) leads to a decline in composite strength due to particle-particle interaction, rather than the desired fiber-matrix interaction. 16,17,29,30 This interaction creates microvoids between the matrix and the fiber, contributing to reduced strength. A challenge in fabricating composites lies in hybridizing uniform and randomly oriented microcellulose, as achieving a consistent distribution within the polymer matrix can be difficult.…”
Section: Tensile Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [ 18 ], showed the physical, mechanical, and moisture absorption properties of Acacia concinna seed powder and Vachellia seed powder reinforced with short Turkish hemp and epoxy resin in their study by producing several matrixes of different weight percentages of seed powders. They observed that the weight percentage of 7.5 showed that the physicomechanical qualities had improved.…”
Section: Introductionmentioning
confidence: 99%
“…This contributes to the overall wettability of the reservoir rock, affects rock−fluid interactions, and potentially influences the oil recovery mechanism. The presence of cellulose-IV at 20.64°in AC indicates the presence of more ordered crystalline regions 39. 3.7. pH and Conductivity.…”
mentioning
confidence: 99%